An Integrative Analysis of Fiqh al-'Ibadah for the Moral Development of Contemporary Muslim Youth: Prayer, Zakat, Fasting, and Hajj - Iqlima Dhuha Anwar; Naufal Firdaus; Aini Fikri (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2025)
This study examines the reactualization of Islamic jurisprudence (fiqh al-'ibadah), specifically prayer (salat), almsgiving (zakat), fasting (sawm), and pilgrimage (hajj), as a framework for moral development among contemporary Muslim youth. Employing a qualitative descriptive-analytical approach, this research explores the spiritual and social dimensions embedded within these four pillars of worship. The findings reveal that fiqh al-'ibadah functions not merely as a procedural guide for ritual observance but also as an instrument for character education and socio-moral reinforcement (fiqh al-akhlaq). Prayer cultivates self-discipline and inner tranquility, zakat strengthens social solidarity and economic justice, fasting fosters self-control and empathy, and pilgrimage reinforces global Islamic brotherhood. This study concludes that an integrative-holistic recontextualization of fiqh al-'ibadah can effectively bridge the knowing-doing gap between ritual knowledge and moral practice The primary contribution of this research lies in offering a comprehensive integrative framework that simultaneously links the four pillars of worship to moral development, addressing the fragmented approach in previous studies. This framework provides Islamic educators and policymakers with a practical model for designing contextual fiqh education for digital-native Muslim youth. However, this study has limitations as library research, it relies entirely on textual analysis without empirical field validation. The theoretical findings require further empirical testing through quantitative or mixed-method studies to measure the actual impact on youth moral behavior. Future research is recommended to conduct longitudinal studies and cross-cultural comparisons to strengthen the generalizability of these findings.